OPTIMAL DESTINATION OFFER IN TERMS REGIONAL INTERNATIONAL AIRPORT (Perner's Contacts, 2012)
Currently a lot of regional international airports deal with problem of operation at least one periodic route to important foreign international airports. This problem can be formulated as the optimization problems since we have to choose the best of solution in terms of previously known the restricted conditions. The presented article aims to show possible application of operational research methods for solving this problem. The article includes four mathematical models usable for the proposal of the optimal destination map.
Keywords: optimization, air transport, regional international airport, mathematical model